URBAN FOLKLORE ON WHEELS: “CHILAKALURIPET RICKSHAW PAINTING PHENOMENON". - Machavarapu, Pavan Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The iconic popular visual representation of cinema and religion through ricksha paintings were unique in Chilakaluripet region. It represents the way of life in coastal region. Regional commercial artist created unique language of rickshaw paintings. This paper explores cultural vibrance in popular art. Many of these paintings are also reflections of the local worship culture. Rickshaw art is personalised bodywork of cycle rickshaws, celebrating of Hand painted visual culture of this region. A Gudu (Top covered) rickshaw is the name given to this kind of vehicle. Along with visuals I also look at the basic functions of these ornamental paintings and themes and the regional culture. I conclude by reviewing recent modifications to modern rickshaw paintings. To uncover more precise information on the work, qualitative research techniques are used.